Os efeitos da sentença declaratória de união estável diante do INSS - Rios, Bruno Carlos dos (2020)
This study evaluates social security effects of the res judicata and the declaratory judgement of stable union recognition, appreciated by the State Common Justice, considering the hypothesis of the National Institute of Social Security (INSS) being not involved in the brought up legal procedural relationship. The fundamental profiles of social security protection aimed at the social welfare of Brazilian society are examined, and both the way the institute of stable union is treated within the homeland legal framework and their legal effects are checked accordingly. The rationality of the managerial understanding of the social security administration, regarding the subject of study, is investigated, since although final judgment stable union by court decision be recognized, INSS, in the administrative field, conditions social security to the presentation of other evidence, inasmuch as social security administration does not accept the effects and authority of the mentioned court decision. Nevertheless, the said administrative requirement visually presents the contradiction of the experience of a state decision-making act, issued by the constitutionally competent court (Judicial Power), recognizing stable union and another state act, of the social security authority responsibility (Indirect Public Administration), which sometimes does not consent to court decision owing to the understanding that stable union between the pensioner and the insured does not exist. To that extent, this work raises the specific objectives of exploring the scope of social security protection of companions, contemplating the extension of the institute of the res judicata within the new Code of Civil Procedure, and finally measuring the level of social security effects of the declaratory judgement of stable union recognition accredited by the State Common Justice. Therefore, in light of current law and mainly considering the 2015 Code of Civil Procedure, the sufficiency, or not, of the declaratory judgement of stable union recognition is examined, so that social security protection is allowed to interested parties. The adjacencies of the social security dependents and the organization of the social security manager are risen, with emphasis on the treatment given by the INSS to the family entity of the stable union, as well as the preclusive effectiveness of the declaratory judgement and its corresponding executive force are discussed. The hypotheses are raised based on doctrinal and jurisprudential research, with the aid of the historical method for searching past episodes related to the topic examined. Hypothetical-deductive methods are considered in situations of eventual gaps in knowledge, and advantage are taken from critical or dialectical methods when no harmony is found, while the inductive method is applied to observe the institute of the res judicata and the legal effects of the declaratory judgement, according to the particularities of legal certainty and the constitutional and procedural assumptions. It is thus intended that the solution for the brought up theme is achieved through the analysis of Law as a unitary system, in which apparent contradictions do not limit themselves to the formalism of maintaining their incongruities